Erbb2 is required for cardiac atrial electrical activity during development - Tenin, Gennadiy; Clowes, Christopher; Wolton, Kathryn; Krejci, Eliska; Wright, Jayne A; Lovell, Simon C; Sedmera, David; Hentges, Kathryn E (PloS one, 2014)
The heart is the first organ required to function during embryonic development and is absolutely necessary for embryo survival. Cardiac activity is dependent on both the sinoatrial node (SAN), which is the pacemaker of heart's electrical activity, and the cardiac conduction system which transduces the electrical signal though the heart tissue, leading to heart muscle contractions. Defects in the development of cardiac electrical function may lead to severe heart disorders. The Erbb2 (Epidermal Growth Factor Receptor 2) gene encodes a member of the EGF receptor family of receptor tyrosine kinases. The Erbb2 receptor lacks ligand-binding activity but forms heterodimers with other EGF receptors, stabilising their ligand binding and enhancing kinase-mediated activation of downstream signalling pathways. Erbb2 is absolutely necessary in normal embryonic development and homozygous mouse knock-out Erbb2 embryos die at embryonic day (E)10.5 due to severe cardiac defects. We have isolated a mouse line, l11Jus8, from a random chemical mutagenesis screen, which carries a hypomorphic missense mutation in the Erbb2 gene. Homozygous mutant embryos exhibit embryonic lethality by E12.5-13. The l11Jus8 mutants display cardiac haemorrhage and a failure of atrial function due to defects in atrial electrical signal propagation, leading to an atrial-specific conduction block, which does not affect ventricular conduction. The l11Jus8 mutant phenotype is distinct from those reported for Erbb2 knockout mouse mutants. Thus, the l11Jus8 mouse reveals a novel function of Erbb2 during atrial conduction system development, which when disrupted causes death at mid-gestation.
Keywords: Animals; myši transgenní; převodní systém srdeční; Heart Defects, Congenital; Mice, Transgenic; Action Potentials; srdeční síně; srdce - funkce síní; Mutation, Missense; Receptor, ErbB-2; Atrial Function; receptor erbB-2; Mice, 129 Strain; missense mutace; Heart Atria; Heart Conduction System; vrozené srdeční vady; zvířata; Mice, Inbred C57BL; myši kmene 129; akční potenciály; myši inbrední C57BL